Phenotypic and Genetic Variation of Some SalviaSpecies Grown in Eastern Anatolia Region of Turkey - AGAR, GULERAY; ADIGUZEL, AHMET; BARIS, OZLEM; GULLUCE, MEDINE; SAHIN, FIKRETTIN (Asian Journal of Chemistry, 2010)
Fatty acid and random amplified polymorphic-DNA (RAPD) profiles were used to examine phenotypic and genetic relationships among 8 Salvia taxa. All the Salvia taxa were used separated based on the presence and composition of 85 different fatty acids. Ten decamer primers were used to find out polymorphism. A total of 33 amplicons in the size range of 360 bp to 2500 bp were produced by ten different primers from the eight Salvia taxa. The results suggested that S. argentea is completely different that other species. Three genetically distinct groups were among the species of Salvia species with high genetic variation. All of Salvia species tested in this study was separated with unique FAME profiles including 86 different fatty acids. This is the first study showing that RAPD and FAME profiles are useful methods for determination of genetic and phenotypic profiles which may be used for identification and characterization of Salvia species.